Emergency endoscopic retrograde cholangiopancreatography in critically ill patients is a safe and effective procedure. Issue 2 (29th November 2012) - Lekharaju, Venkata Pawan Kumar; Iqbal, Javaid; Noorullah, Omar; Polavarapu, Naveen; Menon, Shyam; Hood, Stephen; Stern, Nick; Sturgess, Richard
Abstract : Emergency ERCP may be required in patients with severe cholangitis who rapidly deteriorate with multi-organ dysfunction and who cannot wait until the next available elective list. A significant proportion of patients require ventilatory and inotropic support. We describe our experience on the outcome of emergency ERCP in this cohort of critically ill patients. Medical records of cases undergoing ERCP between November 2008 and November 2011 were retrospectively reviewed. Patients who were in intensive care unit or required general anaesthesia due to haemodynamic compromise at the time of ERCP were included. Total of 2237 ERCPs were performed during this period, of which 36 (2%) emergency ERCP's were performed in 33 patients. The median age was 79 years. All procedures were performed under general anaesthesia in emergency operating room. In 27/36 procedures (75%), the patients required inotropes. Indications included cholangitis (78%), pancreatitis (14%) and post-operative bile leak (8%). Biliary cannulation was achieved in 100% of cases. Endoscopic findings included CBD stones (64%), CBD stones and an additional pathology (8%), bile leak (8%), CBD stricture (5%), Mirizzi's (3%) and blocked plastic stent (3%). In 23/36 (64%) procedures a stent was inserted. In 11/36 (30%) procedures a balloon trawl was sufficient to clear the bile duct. Thirty-day mortality was 25%. Although the 30-day mortality remains high due to multi-organ failure, ERCP is successful and effective in the majority of patients and results in a good outcome for this cohort of critically ill patients, in whom the prognosis is inevitably poor without emergency biliary drainage.